Management and short‐term outcome of malignant colorectal polyps in the north of England1. (25th January 2013) - Gill, M. D.; Rutter, M. D.; Holtham, S. J.
Abstract Aim Management of malignant colorectal polyps (MCP) is contentious, with no randomized controlled trials comparing endoscopic with surgical management. This study reviews the management and outcomes of MCPs across a UK region. Method Patients with a malignant polyp were identified using the NORCCAG (NORthern Colorectal Cancer Audit Group) database between April 2006 and July 2010. All histopathology reports and follow‐up procedures were reviewed. Results Of 386 patients identified, 165 (42.7%) had the polyp biopsied and 221 (57.3%) had an endoscopic local excision (37 piecemeal excision, 184 polypectomy). All patients having an endoscopic biopsy underwent surgery. 103 (46.6%) having a local excision had follow‐up surgery, of whom 79 (76.7%) had no residual cancer. Of the 118 patients managed endoscopically, none had residual cancer on follow‐up endoscopy. The 21 (5.4%) Dukes C cancers were associated with Kikuchi SM3/Haggitt 4 lesions (χ2 = 10.85, P = 0.005) and lesions with an involved/unsure excision margin (χ2 = 7.44, P = 0.017). Predictors of finding residual tumour at surgery after local excision were Kikuchi SM3/Haggitt Level 4 (χ2 = 17.07, P < 0.001) and an involved/unsure excision margin (χ2 = 20.45, P < 0.001). An excision margin > 0 mm was associated with the finding of no residual tumour (χ2 = 25.21, P < 0.001). There was no difference in survival between surgical and endoscopic management (χ2 = 0.634, P = 0.426) after a mean follow‐up of 25.1 months. Conclusion Endoscopic management of a subgroup of MCPs appears safe. A clear resection margin (> 0 mm) appears sufficient to avoid surgery, except in locally advanced lesions (Kikuchi 3/Haggitt 4) which have a greater risk of residual cancer at surgery and lymph node metastasis.